A UTILIZAÇÃO DA LOGÍSTICA NAS EMPRESAS DO RAMO CALÇADISTA VISANDO MELHORAR A COMPETITIVIDADE: Uma pesquisa bibliográfica (REMUNOM, 2024)
Since the beginning of its history, man has been using the logistic process in his activities. However, it was in times of war that logistics became more used and studied, becoming an important tool on the battlefields. Currently it has become increasingly indispensable for organizations in the development of their activities. Like all branches of production, the footwear industry increasingly seeks to use the benefits of good logistics to improve its performance, and thus stand out in the face of the various existing challenges. The present work seeks, through a bibliographic review, to present how logistics has been used throughout the entire production process of companies in the footwear sector and how this has contributed to the improvement of their competitiveness.